A TRANING MANAGEMENT MODEL BASED ON CONTINUOUS PROFESSIONAL DEVELOPMENT FOR ELEMENTARY SCHOOL TEACHERS - Hamid, Abdul (Universitas Negeri Semarang, 2013)
The presence of teachers in the education cannot be separated from the overall good personal life, in the family and in society. Therefore, the teachers have considerable responsibility in creating an effective national life. The responsibility of the teacher in the development of the nation, at least it can be seen from four dimensions, namely the teacher as a person, teachers as an element of a family, teachers as an element of education, and teachers as an element of society. Teacherâ€™s responsibility for the participation in national development must begin with the spirit of nationality itself. Professional competence development in the realm of teachers professionalism is not different in terms of professional development for teachers proposed fixing credit score in terms of promotion Â Professionalism of teachers are required to continuous Â develop in accordance with the times, science and technology, and the needs of the community headway. Including the need for qualified human resources and has the capability to be able to compete in regional forums, national, and international levels. Many things are required to be a professional teacher.